Preliminary Study of Physicists in India 1955 - Planning Commission (Planning Commission Government of India, 1950)
The Preliminary Study of Physicists in India (1955), conducted by the Planning Commission in collaboration with the Indian Statistical Institute and CSIR, examines the demographics, qualifications, employment, specialization, and salary patterns of Indian physicists. The study estimated 4,572 physicists active by 1955, with nearly half registered in the National Register of Scientific and Technical Personnel. While most held master’s degrees from Indian institutions, a substantial portion of doctoral degrees were obtained abroad. Specializations were concentrated in electronics, optics, and nuclear physics, though many physicists did not report a specific field. Employment predominantly occurred in higher education (54%) and government departments (31%), with teaching being the primary function. Salary analysis revealed that research physicists earned progressively higher incomes with age, whereas teachers received comparatively lower salaries. The study underscores gaps in workforce data, uneven distribution of physicists across sectors, and salary disparities, highlighting the need for systematic personnel planning to strengthen India’s scientific and technical capabilities.
Planning Commission Perspective Planning Division
Keywords: Physicists in India; Scientific Manpower; Education; Employment Status; Specialization; Salaries; Research; Teaching; National Register; Higher Education; CSIR; Workforce Planning